Mechatronics: A Foundation Course - de Silva, Clarence W. (CRC Press, 2010)
Designed for students across all of engineering, this text offers the multidisciplinary approach needed to develop a foundation in mechatronics. It covers electrical and mechanical components, sensors and instrumentation, drives and actuators, controls, signal processing, component interfacing, modeling, and design. Practical applications and tools introduced up front are uniformly integrated throughout the book. Cases studies and worked examples that make use of MATLAB, Simulink, and LabVIEW application and case studies are included, as are numerous exercises, most based on real engineering practice.